Research on the Seismic Response Law of Complete Morphology of Butted Well Salt Cavern for Large-Scale Underground Energy Storage - Haitao Li; Dewen Zheng; Kang Li; Qiqi Wanyan; Lina Ran; Yanxia Kou; Song Bai; Jianan Wu; Jianchao Jia; Yunfei Wen; Yuanqing Wang; Hongyan Xing; et al. (Applied Sciences)
The conversion of abandoned butted well salt cavities into underground storage facilities holds immense significance for safeguarding energy security and improving the ecological environment. A significant barrier to the reconstruction of these old cavities is the limited comprehension of their complete morphology, caused by residue coverage. The three-dimensional seismic techniques excel in identifying complex geological structures but have a limited understanding of underground old salt cavity morphology, thus the seismic forward simulation method is utilized to study their seismic response patterns. Based on 3D seismic data, well logging data, and measured cavity shape parameters from the Yexian salt mine region in Henan Province, China, a geological model and observation system were established. The seismic response characteristics of the butted well salt cavern model, encompassing five distinct morphological attributes such as cavity spacing, cavity diameter, cavity height, sediment height, and horizontal connection channel height, were thoroughly investigated. The findings show that the cavity roof exhibits a distinctive “two peaks sandwiching a strong valley” feature, with the positions of the valley and roof remaining aligned and serving as a reliable indicator for identifying the cavity’s top surface. The width of the roof waveform exhibits an exponential amplification effect relative to the cavern width. The residue’s top surface presents an “upward-opening arc” wave peak with a downward shift that diminishes as the residue’s height increases. This peak forms a circular feature with the cavity roof reflection waveform, and the residue’s top surface is always located in the upper half of this circular waveform. The horizontal connection channel’s top and bottom surfaces exhibit contrasting reflection patterns, with the top position aligning with the reflection trough and the bottom reflection waveform shifting downward as the channel height increases. The brine cavern, residue, and bottom of the salt cavern mainly exhibit chaotic reflections. There are distinct identification characteristics on the cavity top, residue top, and connecting channel top in forward simulation. The research findings provide valuable guidance for identifying the morphology of the underground real butted well salt cavity based on 3D seismic data and accelerating the construction of underground energy storage facilities.